High Energy Scattering of Polarized Nucleons with the Phenomenological Spin – Orbit Potential - Xuan, Nguyen Nhu (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abstract: The scattering amplitude of polarized nucleons has been found within the framework of the Klein – Gordon with the phenomenological spin - orbit potential. It has the Glauber type representation. The differential cross sections of polarized nucleon are considered and discussed. The Yukawa potential is applied for this problem to determine the polarization of high energy scattering nucleons.   Keywords: Glauber representation, eikonal scattering theory, polarized nucleons.